Desarrollo de habilidades motrices básicas y su influencia en los fundamentos técnicos del fútbol en niños de 6 a 8 años de la academia Chamo Flores, 2023- 2024. - Macas Cuenca, Anderson Emilio (2024)
The present work of curricular integration was carried out with the general objective to analyze the relationship of the influence of the basic motor abilities on the development of the technical football fundamentals in children of the Chamo Flores Football Academy, in Loja city. With basis on this, two variables to be analyzed were raised; they were the basic motor abilities and the technical football fundamentals. The applied methodology in the investigation had a combined focus with a correlational research scope, with the support of scientific methods, like inductive, deductive, statistical and teaching. The assessment instruments were a survey, which was applied to the teachers and a post-test for each technical football fundamental, which was applied to the children. These instruments permitted to measure the level of incidence of the motor development on the performance of the technical football fundamentals. In the pre-test stage the results indicated that the children did not have a good coordination or balance; hence, there was a bad technical implementation of the fundamentals. Based on the results, a training plan, which was focused on the basic motor skills and the technical fundamentals, was designed and applied. This plan was structured in 24 training sessions. It was concluded that the planned work helped to improve the level of the basic motor abilities permitting to enhance also the technical football fundamentals and reaching the score of very good and excellent. Keywords: training plan, basic motor abilities, technical football fundamentals.